The Foundation of Philosophical Thought - Chauhan, Sejal V. (Journal of Social Science and Humanities, 2025)
Upanishads are late Vedic and post Vedic Sanskrit texts that document the transition from the archaic ritualism etc., Etymologically Upanishads means in Sanskrit “Sitting near” (i. e. at the feet of the master) from upa ‘near’ + ni - sad (sitnear). This no doubt means the pupils sitting near the teacher and implies studying with the spiritual teacher. These contains the central teachings of Hinduism. Nobody has written the Upanishads. It is the eternal philosophy which is ever flowing. It is the intimate part of the Vedas from the beginning. Vedvyas compiled the Vedas) four in number). Brahmanas is the God of Vedas and is exclusively discussed in the early Upanishads.